Inflammation and Bone Repair: From Particle Disease to Tissue Regeneration - Goodman, Stuart B.; Pajarinen, Jukka; Yao, Zhenyu; Lin, Tzuhua (Frontiers in Bioengineering and Biotechnology, 2019)
When presented with an adverse stimulus, organisms evoke an immediate, pre-programmed, non-specific innate immune response. The purpose of this reaction is to maintain the organism’s biological integrity and function, mitigate or eradicate the injurious source, and re-establish tissue homeostasis. The initial stage of this protective reaction is acute inflammation, which normally reduces or terminates the offending stimulus. As the inflammatory reaction recedes, the stage of tissue repair and regeneration follows. If the above sequence of events is perturbed, reconstitution of normal biological form and function will not be achieved. Dysregulation of these activities may result in incomplete healing, fibrosis, or chronic inflammation. Our laboratory has studied the reaction to wear particles from joint replacements as a paradigm for understanding the biological pathways of acute and chronic inflammation, and potential translational treatments to reconstitute lost bone. As inflammation is the cornerstone for healing in all anatomical locations, the concepts developed have relevance to tissue engineering and regenerative medicine in all organ systems. To accomplish our goal, we developed novel in vitro and in vivo models (including the murine femoral continuous intramedullary particle infusion model), translational strategies including modulation of macrophage chemotaxis and polarization, and methods to interfere with key transcription factors NFB and MyD88. We purposefully modified MSCs to facilitate bone healing in inflammatory scenarios: by preconditioning the MSCs, and by genetically modifying MSCs to first sense NFB activation and then overexpress the anti-inflammatory pro-regenerative cytokine IL-4. These advancements provide significant translational opportunities to enhance healing in bone and other organs.